Extended Data Figure 7 – Source Data (corticocortical L2/3 synaptic transmission in Wfs1-CreERT2 mice) - Jinseon Yu (22598699) (2025)
This dataset contains the raw numerical values used to generate Extended Data Figure 7, which examines cortico–cortical (layer 2/3 → layer 2/3) synaptic transmission in Wfs1-CreERT2 mice following repeated ketamine administration. Included data: - Peak amplitude of optogenetically evoked EPSCs recorded at 0.1 Hz stimulation (Panel 7C) - Short-term plasticity during 10 Hz stimulation, with EPSC amplitudes normalized to the first response (Panel 7D) Structure: - The worksheet includes raw EPSC amplitudes at 0.1 Hz and normalized EPSC amplitudes across 10 Hz trains. - These values correspond to the synaptic physiology data shown in Extended Data Figure 7.